The dark side of emotional labour of South African Police Service officers, working in KwaZulu-Natal - Thwala, Fezeka Asande (Rhodes University, Faculty of Humanities, Department of Sociology)
This research paper explores the concept of emotional labour through the lens of the dark side of emotional labour, which includes emotions such as anger, aggression, intimidation, and neutrality. The concept of the dark side of emotional labour seeks to investigate the experiences and effects the performance of these emotions has on police officers as required by the SAPS organisation. These experiences are explored using three central themes: emotional neutrality, emotional toxicity, and emotionally dirty work. This paper places emphasis on emotional labour not only restricted to the performance of positive emotions such as smiling and presentable appearance such as Arlie Hochschild (1983) account of air hostesses but also extending to the expectation or requirement for the performance of dark emotions, which is quite evident in the case of police officers. This study was conducted in KwaZulu Natal, with Police Officers that have acquired the necessary training to be police officers and have worked a minimum of 2 years. The research methodology used was qualitative, and data were obtained from semi-structured interviews. These were then analysed and presented in line with the research objectives. The research found evidence of how individuals' different positions influence how frequently they perform and express negative emotions. It found that the gender difference also contributes to the diverse experiences of dark emotions. Furthermore, it found that the continuous experience of negative emotions has, to an extent, affected the police officers in their lives outside of the organisation. This study concluded by discussing the implications and recommendations for further research.
Keywords: Police -- South Africa; Police Attitudes; Police Job stress -- South Africa KwaZulu-Natal; Police psychology -- South Africa KwaZulu-Natal; Police Social conditions; Anger; Aggressiveness; Intimidation; Employee morale -- South Africa KwaZulu-Natal; Work environment -- South Africa KwaZulu-Natal; Corporate culture -- South Africa KwaZulu-Natal